PENYULUHAN DAN PELATIHAN PEMBUATAN MASKER RAMBUT DAUN PEPPERMINT DI DESA CIBIRU WETAN KABUPATEN BANDUNG - Devianti Sagita, Novaliana; Nisrina Anbar Fatin, Mia; Saidah, Siti; Andriansyah, Ivan (Jurnal Adiguna Pengabdian Masyarakat, 2024)
The village of Cibiru Wetan is known for its active community involvement through various working groups (pokja). One such group is the Family Medicinal Plants (TOGA) pokja, dedicated to cultivating plants at home for their medicinal benefits. TOGA plants are utilized not only for disease prevention (preventive), health promotion (promotive), disease treatment (curative), and health recovery (rehabilitative), but also for developing cosmetic products. Among the TOGA plants targeted for cosmetic development is peppermint leaf. Peppermint leaves are known to promote hair growth, prevent hair loss, reduce excess oil, alleviate scalp itchiness, and strengthen hair roots. Objective: This community service program aims to apply the cultivation of TOGA plants, particularly peppermint, as an additive in hair masks for the community of Cibiru Wetan village. Methodology: The implementation of this community service program includes the introduction, utilization, and processing of peppermint leaves into hair masks usable by the general public, with a focus on the residents of Cibiru Wetan village. Results: Through the execution of this engagement program, community knowledge has been enhanced in utilizing TOGA, specifically peppermint leaves, as an ingredient in hair masks for the residents of Cibiru Wetan village. Outcome Targets: This initiative endeavors for the residents of Cibiru Wetan village to learn how to utilize peppermint leaves effectively in hair masks, with the expectation of contributing to economic improvement within the community.